Feasibility of a multifaceted educational strategy for strengthening rural primary health care - Hortensia Reyes-Morales; Enrique Gómez-Bernal; Gaudencio Gutiérrez-Alba; Arturo Aguilar-Ye; José Arturo Ruiz-Larios; Gabriel de Jesús Alonso-Núñez (Instituto Nacional de Salud Pública, 2017)
Objective. To evaluate the feasibility and acceptability of a comprehensive educational strategy designed to improve care quality in rural areas of Mexico. Materials and methods. A demonstration study was performed in 18 public rural health centers in Mexico, including an educational intervention that consists of the following steps: Development of the strategy; Selection and training of instructors (specialist physicians from the referral hospital and multidisciplinary field teams); Implementation of the strategy among health care teams for six priority causes of visit, through workshops, individual tutorials, and round-table case-review sessions. Feasibility and acceptability were evaluated using checklists, direct observation, questionnaires and in-depth interviews with key players. Results. Despite some organizational barriers, the strategy was perceived as worthy by the participants because of the personalized tutorials and the improved integration of health teams within their usual professional practice. Conclusion. The educational strategy proved to be acceptable; its feasibility for usual care conditions will depend on the improvement of organizational processes at rural facilities.